Would Cain Plead Guilty to the Murder of Abel? On the Historical Transformation of the English and American Trial Model as a Source of Plea Bargaining (Ius Novum, 2026)
The article presents a historical-legal analysis of the evolution of the Anglo-Welsh and American criminal process in the context of those elements of both models that determined that it was the common law legal culture that developed the phenomenon of plea bargaining. The results of British research are presented, showing that the shape of the criminal procedure of England and Wales, as late as the turn of the eighteenth and nineteenth centuries, differed significantly from the now-familiar purely adversarial model, characterised by the high involvement of professional representatives of the parties, the inactivity of the defendant and the passivity of the court in the course of the trial. As pointed out, it was the adversarial transformation of English procedure observed in particular since the early nineteenth century, affecting the decline in the previous effectiveness of the jury trial, that led to the development of plea bargaining. The different origins of consensual procedural institutions in the United States of America, as compared with the system of England and Wales, are also discussed.
Keywords: consensualism, adversarialism, plea bargaining, criminal trial